BIBLICAL VIEW OF RELIGION AND POLITICS - Gomes, Theotonius (Journal of Dharma, 2000)
Throughout history religion and politics have been essential and key elements of human life. The interplay between religion and politics in human societies, more than any other aspects of human life, has been very active factor. Often the two have been in both ideological and in practical order very amiable, but often too at conflicts and at odds, trying to overpower each other even with violence. It is very auspicious of the present times that most of human factors, including religion and politics, have been able to enter into a spirit of communion through mutual dialogue. We welcome this development and desire that it be brought to happy and fruitful conclusion.